Methylation of geometrically constrained lysine analogues by histone lysine methyltransferases. Issue 20 (12th February 2020) - Al Temimi, Abbas H. K.; White, Paul B.; Mulders, Marcus J. M.; van der Linden, Nicole G. A.; Blaauw, Richard H.; Wegert, Anita; Rutjes, Floris P. J. T.; Mecinović, Jasmin
Abstract : Histone lysine methyltransferases (KMTs) exhibit substrate specificity for lysine and its geometrically constrained mimics. Abstract : We report synthesis and enzymatic assays on human histone lysine methyltransferase catalysed methylation of histones that possess lysine and its geometrically constrained analogues containing rigid ( E )-alkene (K E ), ( Z )-alkene (K Z ) and alkyne (Kyne ) moieties. Methyltransferases G9a and GLP do have a capacity to catalyse methylation in the order K ≫ K E > K Z ∼ Kyne, whereas monomethyltransferase SETD8 catalyses only methylation of K and K E .